Soil nematodes show a midelevation diversity maximum and elevational zonation on Mt. Norikura, Japan - Dong, Ke; Moroenyane, Itumeleng; Tripathi, Binu; Kerfahi, Dorsaf; Takahashi, Koichi; Yamamoto, Naomichi; An, Choa; Cho, Hyunjun; Adams, Jonathan (Nature Publishing Group, 2017)
Little is known about how nematode ecology differs across elevational gradients. We investigated the soil nematode community along a ~2,200 m elevational range on Mt. Norikura, Japan, by sequencing the 18S rRNA gene. As with many other groups of organisms, nematode diversity showed a high correlation with elevation, and a maximum in mid-elevations. While elevation itself, in the context of the mid domain effect, could predict the observed unimodal pattern of soil nematode communities along the elevational gradient, mean annual temperature and soil total nitrogen concentration were the best predictors of diversity. We also found nematode community composition showed strong elevational zonation, indicating that a high degree of ecological specialization that may exist in nematodes in relation to elevation-related environmental gradients and certain nematode OTUs had ranges extending across all elevations, and these generalized OTUs made up a greater proportion of the community at high elevations – such that high elevation nematode OTUs had broader elevational ranges on average, providing an example consistent to Rapoport’s elevational hypothesis. This study reveals the potential for using sequencing methods to investigate elevational gradients of small soil organisms, providing a method for rapid investigation of patterns without specialized knowledge in taxonomic identification.